(3eeOhO GHf OQjOs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3dGJQcff Edi Gdghi hGPcQ eaGQbI GdghGA jhekG JUjQ Edi GdKQi hjahR ZjQc HGdKQGA s
(3BNQgG (B:s
(3hCRGc JfXQ cGdSeGA dCNjQ ai fXQ GdSeGA TeS GdVMi WdYJ Ydjc hdGJQi TeS GdVMGA JeJ GdbUjOI GdeeOhOI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs